SNPs analysis of height traits in Ningqiang pony. Issue 5 (1st October 2021) - Bai, Hao; Lu, Hongzhao; Wang, Ling; Wang, Shanshan; Zeng, Wenxian; Zhang, Tao
Abstract: Ningqiang pony is one of the five pony breeds in China and is listed as a rare species. It is, therefore, meaningful to conduct stature research on this breed for its efficient reproduction, utilization and protection. This study is based on four SNP variants of adjacent LCORL/NCAPG, HMGA2, ZFAT and LASP1 genes, which have been found to be associated with horse height, and then, the 4 SNP loci in 22 Ningqiang ponies were analyzed. The results showed that there were genetic variations at the four loci in Ningqiang pony, there was a SNP on LCORL/NCAPG, HMGA2 and ZFAT gene all including T allele and C allele and LASP1 including A allele and G allele. Further data analysis revealed that LCORL/NCAPG variant harbor the allele T and LASP1 variant harbor the allele G were significantly related to body height ( p  < 0.05). These findings suggested that the two SNP mutations within the LCORL/NCAPG and LASP1 genes could be considered as a screening marker for the body height of Ningqiang pony and could provide a new strategy for breeding and protect the rare germplasm resources.